Impact of Very Small Aneurysm Size and Anterior Communicating Segment Location on Outcome after Aneurysmal Subarachnoid Hemorrhage. Issue 2 (17th November 2022) - Roethlisberger, Michel; Aghlmandi, Soheila; Rychen, Jonathan; Chiappini, Alessio; Zumofen, Daniel W.; Bawarjan, Schatlo; Stienen, Martin N.; Fung, Christian; D'Alonzo, Donato; Maldaner, Nicolai; Steinsiepe, Valentin K.; Corniola, Marco V.; et al.
Abstract : BACKGROUND: Very small anterior communicating artery aneurysms (vsACoA) of <5 mm in size are detected in a considerable number of patients with aneurysmal subarachnoid hemorrhage (aSAH). Single-center studies report that vsACoA harbor particular risks when treated. OBJECTIVE: To assess the clinical and radiological outcome(s) of patients with aSAH diagnosed with vsACoA after aneurysm treatment and at discharge. METHODS: Information on n = 1868 patients was collected in the Swiss Subarachnoid Hemorrhage Outcome Study registry between 2009 and 2014. The presence of a new focal neurological deficit at discharge, functional status (modified Rankin scale), mortality rates, and procedural complications (in-hospital rebleeding and presence of a new stroke on computed tomography) was assessed for vsACoA and compared with the results observed for aneurysms in other locations and with diameters of 5 to 25 mm. RESULTS: This study analyzed n = 1258 patients with aSAH, n = 439 of which had a documented ruptured ACoA. ACoA location was found in 38% (n = 144/384) of all very small ruptured aneurysms. A higher in-hospital bleeding rate was found in vsACoA compared with non-ACoA locations (2.8 vs 2.1%), especially when endovascularly treated (2.1% vs 0.5%). In multivariate analysis, aneurysm size of 5 to 25 mm, and not ACoA location, was an independent risk factor for a new focal neurological deficit and a higher modified Rankin scale at discharge. Neither very small aneurysm size nor ACoA location was associated with higher mortality rates at discharge or the occurrence of a peri-interventional stroke. CONCLUSION: Very small ruptured ACoA have a higher in-hospital rebleeding rate but are not associated with worse morbidity or mortality.